Analisis Strategi Perkembangan Ekonomi Berkelanjutan - Rona Malum Berutu; Samuel Ganda Putra Siregar; Seyla Ratna Sari Simanjuntak (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
This paper examines sustainable economic development strategies with a focus on community empowerment and local economic independence. This research aimed to provide a holistic and integrated view of sustainable economic development. Researchers used a qualitative descriptive method to evaluate economic development programs in Central Java, Indonesia. The results indicate that sustainable economic development requires a holistic and integrated strategy that encompasses various aspects of local community life, such as economic, social, cultural, and environmental needs. Community empowerment through active community participation in the planning and implementation of economic development programs is crucial for achieving local economic independence. In this paper, the authors propose a sustainable economic development strategy based on the concept of community participation and empowerment. This strategy involves utilizing local resources, strengthening associations and cooperatives, empowering women and youth, developing the agricultural sector, small and medium-sized industries, and sustainable environmental management. In conclusion, sustainable economic development can be achieved through a holistic and integrated strategy, focusing on community empowerment and local economic independence. This strategy can encourage sustainable economic development and improve community welfare.